Pharmacology and Distribution of Norepinephrine Transporters in the Human Locus Coeruleus and Raphe Nuclei - Ordway, Gregory A. (J Neurosci, 1997)
The norepinephrine transporter (NET) is a site of action for tricyclic antidepressant drugs and for drugs of abuse such as amphetamine and cocaine. In this study, the binding of [(3)H]nisoxetine to NETs in the noradrenergic cell group, the locus coeruleus, and the serotonergic cell groups, the dorsal raphe nuclei, was measured autoradiographically in postmortem human brain. [(3)H]nisoxetine binding was unevenly distributed along the rostral–caudal axis of the locus coeruleus and correlated positively with numbers of neuromelanin-containing (noradrenergic) cells along the axis of the locus coeruleus within individuals. Binding densities of [(3)H]nisoxetine in dorsal raphe nuclei were similar to that in the locus coeruleus. [(3)H]nisoxetine binding was unevenly distributed along the entire rostral–caudal extent of the dorsal raphe, with the highest binding occurring in the interfascicular and ventral nuclei. A moderate amount of [(3)H]nisoxetine binding was also observed in the median raphe nucleus. The specificity of [(3)H]nisoxetine binding to NETs in monoaminergic nuclei was assessed by measuring the inhibition of its binding by desipramine, imipramine, or citalopram. The order of affinities of these drugs was identical in the locus coeruleus and dorsal and median raphe and was characteristic of binding to NETs (desipramine > imipramine > citalopram). Thus, high levels of NETs and an uneven distribution of NETs occur in the locus coeruleus as well as in the dorsal raphe nuclei of the human.